Aus der Geschichte der entomologischen Sammlungen des ehemaligen Deutschen Entomologischen Instituts. III. Die Hymenopterensammlung. - Rohlfien, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1979)
The third part of the contributions to the history of the entomological collections of the former Deutsches Entomologisches Instiut (now Department of Taxonomy of Insects of the Institute of Plant Protection Research) covers the development of the collection of Hymenoptera. The different parts of the collection the means of aquisitoin, the curators, the present state of the collection and its future functions are discribed.